Analysis of Hardness, Quality and Fluidity Al-Si Casting Result by Using Clamshell (Placuna placenta) as The Mixture of Sand Moulding - SMSN Shikh Zahari; Saif Aziz Saputra; Putut Murdanto (Universitas Negeri Malang, 2018)
Metal is an element that cannot be separated from human life. Almost all of human activities includes metal element in it. Metals can be formed through several ways, one of which is metal casting. Metal casting is one of technique in producing products where the metal was melted in crucible and then poured in a moulding which is similar to the original shape of the product. Moulding that are commonly used are sand moulding. Commonly, binder which used in sand casting process is bentonite. Bentonite, was kind of mineral which can be run out during its usage. This study aimed to analyse the alternative binder to reduce the usage of bentonite. This study analysed the using of clamshell as the mixture of moulding sand against the hardness, quality and fluidity of Al-Si casting result. The highest hardness value was found at the specimen with the mixture of 11% clamshells with an average hardness value of 122.96 HV. The highest value of fluidity also presented in the specimen which used mixture of 11% clamshells that resulted the length of specimen at 789 mm. Based on the analysis of casting defect showed that specimen which used 5% clamshells had the fewest and the smallest defect compared the other specimens.